The influence of cognitive load on maternal postural sway and heart rate in response to infant vocalizations. Issue 6 (24th February 2020) - Hiraoka, Daiki; Nomura, Michio
Abstract: Infants communicate their emotions to their caregivers through cries and laughter. Recent work suggests that adaptive parenting requires cognitive regulation of intuitive behaviors toward infants' signals. In this study, we examined the effects of cognitive regulation on mothers' unconscious behavioral and cardiac responses to infant cries and laughs. In all, 55 mothers took part in this study. To manipulate cognitive load, mothers were asked to memorize alphabet characters (two letters in the low cognitive load condition and eight in the high cognitive load condition). Then, they heard infant vocalizations (cries or laughs) for 6 s. During this time, we measured mothers' behavioral (center of pressure, an index of approach–avoidance behavior) and physiological (heart rate) responses. Regardless of vocalization type (infant cries or laughs), high cognitive load increased mothers' forward movement toward the infant sounds as well as mothers' heart rate. These findings advance our understanding of the link between executive function and maternal response to infant signals by utilizing postural and physiological measures of maternal response during memory tasks that require cognitive resources.